(untitled) (Journal of Hama University, 2019)
This study is conducted at Job Ramlah Dairy station belonging to the general organization of cattle in Hama on the records of 145 Friesiancows distributed on three groupswere (1) imported grandmother cattle, (2) domestic born mother cattle, and (3) domestic born daughter cattle, for studying some productive qualities of milk. The results shows significant differences in milk season, between the second and the third group, while it is not significant differences between the first and the second group, also the first and the third group. the second group recorded the longest period of milk season as compared with the other groups. But the first group records the highest value of Arithmetic mean of total milk Yield, and shows significant differences between the first and the second groups, while there is no significant between the first and the second group, and the second and the third group. As well, the difference shows no significant differences of Dry Period length between the groups. Results from this study refer to the ability of the imported Friesian cattle of acclimatization with the new environment,so the production qualities of the domestic born cattle are similar to imported one.